Classification of Children's Heart Sounds With Noise Reduction Based on Variational Modal Decomposition - Zhang, Anqi; Wang, Jiaming; Qu, Fei; He, Zhaoming (Frontiers in Medical Technology, 2022)
Purpose Children's heart sounds were denoised to improve the performance of the intelligent diagnosis. Methods A combined noise reduction method based on variational modal decomposition (VMD) and wavelet soft threshold algorithm (WST) was proposed, and used to denoise 103 phonocardiogram samples. Features were extracted after denoising and employed for an intelligent diagnosis model to verify the effect of the denoising method. Results The noise in children's phonocardiograms, especially crying noise, was suppressed. The signal-to-noise ratio obtained by the method for normal heart sounds was 14.69 dB at 5 dB Gaussian noise, which was higher than that obtained by WST only and the other VMD denoising method. Intelligent classification showed that the accuracy, sensitivity and specificity of the classification system for congenital heart diseases were 92.23, 92.42, and 91.89%, respectively and better than those with WST only. Conclusion The proposed noise reduction method effectively eliminates noise in children's phonocardiograms and improves the performance of intelligent screening for the children with congenital heart diseases.